2012
DOI: 10.1007/978-3-642-31155-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Rumor Spreading in Preferential Attachment Graphs

Abstract: We show that the asynchronous push-pull protocol spreads rumors in preferential attachment graphs in time O(√ log n) to all but a lower order fraction of the nodes with high probability. This is significantly faster than what synchronized protocols can achieve; an obvious lower bound for these is the average distance, which is known to be Θ(log n/ log log n) for preferential attachment graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Indeed, the connectivity of the graph has a great impact on the efficiency of the uniform random algorithm. Many papers analyzed the uniform random algorithm with respect to some notion of connectivity [10,37,23,44,24], and additional papers studied other algorithms for information spreading [9,15,16,18] and additional problems [31,32], as well as different families of graphs [13,14,19] or with respect to different graph parameters [17].…”
Section: The Gossip Model and Spannersmentioning
confidence: 99%
“…Indeed, the connectivity of the graph has a great impact on the efficiency of the uniform random algorithm. Many papers analyzed the uniform random algorithm with respect to some notion of connectivity [10,37,23,44,24], and additional papers studied other algorithms for information spreading [9,15,16,18] and additional problems [31,32], as well as different families of graphs [13,14,19] or with respect to different graph parameters [17].…”
Section: The Gossip Model and Spannersmentioning
confidence: 99%
“…Distancebased bounds were given for nodes placed with uniform density in R d [30,31], which also address gossip-based solutions to specific problems such as resource location and minimum spanning tree. Doerr, Fouz, and Friedrich [12,13] have recently presented algorithms for fast information spreading in preferential attachment graphs, which model social networks. Spreading in social networks was also analyzed in [19].…”
Section: Related Workmentioning
confidence: 99%
“…For the asynchronous push-pull protocol there exists much less literature [14,18], mostly devoted to models for scale-free networks. In [14] it was shown that on preferential attachment graphs a rumor needs a time of O( ln(n)) w.h.p.…”
Section: Related Workmentioning
confidence: 99%
“…In [14] it was shown that on preferential attachment graphs a rumor needs a time of O( ln(n)) w.h.p. to spread to almost all nodes.…”
Section: Related Workmentioning
confidence: 99%